2013
DOI: 10.1021/jo400503f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cascade Reactions of 1-(3-Arylprop-2-ynyloxy)-2-bromo Benzene Derivatives with Organoboron Compounds

Abstract: Applications of the cascade cyclocarbopalladation reaction followed by Suzuki-Miyaura coupling reactions of the readily available aryl-substituted propargylic aryl ethers with arylboronic acid and potassium trans-β-styryltrifluoroborate accomplish a new versatile entry in the synthesis of benzofuran derivatives. Notably, a new approach to the challenging synthesis of C3 functionalized 2-unsubstituted benzofurans has been developed by a cyclocarbopalladation/cross-coupling/aromatization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Finally, we also tested this isomerization with stoichiometric amounts of bases such as K 3 PO 4 in DMF at 100 °C (Table 1, entry 10). Although, this strategy has been reported for the synthesis of 3‐substituted benzofuran derivatives,15 it did not work for the synthesis of indole derivative 3a . These results demonstrated that Fe(OTf) 3 has higher catalytic activity for this transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also tested this isomerization with stoichiometric amounts of bases such as K 3 PO 4 in DMF at 100 °C (Table 1, entry 10). Although, this strategy has been reported for the synthesis of 3‐substituted benzofuran derivatives,15 it did not work for the synthesis of indole derivative 3a . These results demonstrated that Fe(OTf) 3 has higher catalytic activity for this transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic compounds play important roles as intermediates in organic synthesis, as the reactive functional groups (e.g. nitro, 1 aldehyde, 2 and bromo 3 ) on aromatic rings have been widely utilized for over a century as key chemicals for the synthesis of explosives, 4 dyes, 5 pharmaceuticals, 6 and polymers. 7 Meanwhile, polyhedral oligomeric silsesquioxanes have been well recognized as useful nanosized building blocks in the synthesis of organic-inorganic hybrid materials due to their versatile structure consisting of an inorganic Si-O-Si core and peripheral organic functional groups.…”
mentioning
confidence: 99%
“…As imilar strategyw as employed af ew years earlier by Arcadi et al in the synthesis of 3-ylidene-dihydro- benzofurans 26 from 2-aryl propargyl ethers 25 (Scheme 6). [16] Thea uthors propose a5 -exo-dig carbopalladation at the alkyne,f ollowed by the Suzuki coupling of the arylboronic acid. Va riation on R 1 was limited as was Ar 1 ,w hile both para and meta substituents on the arylboronic acid were tolerated.…”
Section: Carbopalladation/suzuki Couplingmentioning
confidence: 99%